PAK dan Pemuda: Menjawab Tantangan Generasi Milenial - Martinus Sulang; Kezia A. Oni Eki; Sandra R Tapilaha (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
The challenges of millennials cover various aspects such as economy, employment, property ownership and leadership. According to Glints, the first challenge millennials face is economic, caused by the impact of previous economic crises and capital losses. In the world of work, millennials are often associated with stigmatization in the workplace and cross-generational differences in working styles, which can be challenging. Property ownership is also a challenge due to the high consumption of millennials. Managers need to be able to adapt to change and not feel stressed as millennials are more likely to seek real work and get bored quickly in the workplace. Millennials also value their own experiences and strengths, so they need to focus on that. This research uses a qualitative approach. This article uses library inquiry techniques, or library investigation, to copy data and understand theories found in relevant literature. The data used for this purpose is undoubtedly a precedent study of related arguments, such as libraries, journals, and scientific articles. Christian Religious Education (CHE) plays a crucial role in holistic education. Through PAK, millennials are guided to cultivate Christian values such as love, peace, honesty and justice. It also plays a role in shaping a moral and virtuous character based on the example of Jesus Christ. In addition, PAK equips millennials with a strong moral and ethical foundation, helps them make responsible and moral decisions, and guides them to live their lives in accordance with Christian values. In today's digital era, Christian Religious Education (CHE) needs to adapt to the technology used in students' lives. This is important to ensure that learning is not boring and can engage students. In addition, Christian Religious Education should also shape students' self-image according to the values of biblical truth. In this way, students can develop a strong character based on Christian faith. PAK in its ministry should encourage every believer, from children to adults, so that they can use and optimize their intelligence/knowledge for the common good Christian Religious Education (CHE) in the modern era faces the challenge of educating the millennial generation which has unique characteristics. This generation is accustomed to technology and has high self-confidence. Therefore, PAK needs to adapt to the technology used in students' lives to ensure that learning is not boring and engaging. In addition, PAK should focus on building students' self-awareness according to the values of Biblical truth and Christian Religious education teaching. This is important to help students develop a strong character based on the Christian faith. In this way, PAK can have a positive impact on the millennial generation and help them become people of faith and morals in an increasingly modern world.